LEXICAL COHESION FOUND IN THE JAKARTA POST - Fizi, Ridhani (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2022)
ABSTRACT This research analyzes about lexical cohesion found in Opinion Column of The Jakarta Post. Lexical cohesion is the central devices for making texts hang together. Lexical cohesion is the way to know how the relationship from one word to another word in the text and lexical cohesion gives the most substantive contribution to the text. By this research is expected to understand and to know the relationship of the word in the text especially the text of Opinion Column of The Jakarta Post. To conduct this research the researcher uses descriptive qualitative method, because the data are in words, phrases, and sentences. The data of this research are opinion column of The Jakarta Post that they are: The Urgency of Economic Democratization, Mediating Indonesia Democracy: The Critical Role of The Media, Humanizing Our Hospitals: Start with Services, Islamic Parties at an Impasse, Need Reform to Avoid The Worst, Protecting The informal Sector in southeast Asia’s Megacities and APEC Summit Will Speed up Economic Integration. To analyze the data the researcher takes the data which consist of reiteration and collocation that are used in The Jakarta Post especially on opinion column. The result of this research show that lexical cohesion which consists of reiteration and collocation is used in The Jakarta Post’s Opinion Column and each kind of lexical cohesion has different function. By using lexical cohesion, the Jakarta Post’s opinion column has words are not monotonous to read. Finally, this research gives contribution to English students, lecturers and people who are interested in analyzing about lexical cohesion; because this study can lead the reader understand the relationship of the words in the text. For the next researches which have the same interest to analyze lexical cohesion, this research is expected that the result of the study is going to lead the next researcher as reference and comparison that might be relevant to their research. Hopefully, further researchers can analyze more deeply and use the new theory of lexical cohesion. Key Term: Lexical Cohesion, Reiteration, Collocation